The play of Mahamudra: spontaneous teachings on Virupa's mystical songs - Mig-dmar-tshe-brtan ca. 20./21. Jh. (Wisdom, 2021)
Completely pure by nature, like space -- Not eternal, not annihilated -- Not apparent, not empty -- Not real, not unreal, not nonarising -- Not beyond mind -- Not nonbeing -- Those false horns of a rabbit -- Innate from the beginning, not to be sought elsewhere -- Empty throughout all time and always selfless -- The play of Mahamudra, the original dharmata -- onnected with the sublime guru -- Since one is free from all attachment -- Thoughts arise in the mind like a stream -- Rest in the undistracted state -- Though it seems a particle is in the eye -- Just as a good horse is encouraged -- Giving up nothing, accomplishing nothing -- Give up attachment and aversion -- Think on the great benefit of migrating beings -- Difference is liberated in its own state -- Since realism is destroyed in its own state -- Who realizes selflessness? -- Nothing exists in peaceful and pure space.